Kerr nonlinearity-assisted quadratic microcomb - Wang, Ke; Li, Jing; Dai, Fan; Wang, Mengshuai; Wang, Chuanhang; Wang, Qiang; Tu, Chenghou; Li, Yongnan; Wang, Hui-Tian (Frontiers in Physics, 2022)
Generation of nonlinear frequency combs in χ(3) optical microresonators has attracted tremendous research interest during the last decade. Recently, realization of the microcomb owing to χ(2) optical nonlinearity in the microresonator promises new breakthroughs and is a big scientific challenge. Moreover, it is of high scientific interest that the presence of both second- and third-order nonlinearities results in complex cavity dynamics. In particular, the role of χ(3) nonlinearity in the generation of the quadratic microcomb is still far from being well understood. Here, we demonstrate the interaction between the second- and third-order nonlinearity in the lithium niobate microresonator, which can provide a new way of phase matching to control the mode-locking condition and pulse number for the quadratic microcomb. Our results verify that the Kerr nonlinearity can benefit the quadratic microcomb. The principle can be further extended to other material platforms to provide more manipulation methods for comb generation based on χ(2) nonlinearity at mid-infrared.